Fiber optic displacement sensor based on micro-thickness measurement using bundled fiber and concave mirror - Yasin, Moh; Harun, Sulaiman Wadi; Ahmad, Harith (INOE, 2011)
In this paper, we propose and demonstrate a simple yet accurate optical fiber based sensor capable of performing micron and sub-micron thickness measurement. The proposed sensor is based on reflective displacement sensor, which consists of a 785 nm light source, multimode plastic bundle fiber probe, a concave mirror target and a silicon detector. A mechanical chopper is used in conjunction with lock in amplifier to allow sensitive detection free from ambient light interference. The thickness of the sample can be obtained from a linear equation correlating the thickness of the sample to the displacement of the sensor at which the peak output voltage is obtained, or by correlating the thickness of the sample directly to the peak output voltage measured. The sensitivity of the sensor is obtained at 1.0188mV/mm in the range of 0-0.64 mm of cover slips thickness.